Protestantyzm a ekumenizm - Bugajski, Jarosław (Slavia Centralis, 2020)
Protestantism is a concept describing religious movements originating directly or indirectly from the 16th-Century Reformation led by Martin Luther. Rejecting the primacy and the hierarchy of authority forced Luther to formulate new, completely different structures for the Reformed Churches. The contemporary ecumenical movement had its beginnings in Evangelical Christianity in the 19th Century; however, only in the 20th Century we can speak of a truly ecumenical movement comprising multiple religious beliefs. The Christians from the Protestant communities and churches made first steps towards the ecumenical dialogue. The main task of the ecumenical movement is to work out a common, Christian response to the social, economic and cultural changes that are the source of pain and humiliation for many people, not only the Christians.